2020
DOI: 10.3390/w12030666
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Effects of Climate Change on Reference Evapotranspiration Using the HadCM3 and LARS-WG

Abstract: This study evaluates the effect of climate change on reference evapotranspiration (ET0), which is one of the most important variables in water resources management and irrigation scheduling. For this purpose, daily weather data of 30 Iranian weather stations from 1981 and 2010 were used. The HadCM3 statistical model was applied to report the output subscale of LARS-WG and to predict the weather information by A1B, A2, and B1 scenarios in three periods: 2011–2045, 2046–2079, and 2080–2113. The ET0 values were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…GCMs are the most reliable tools for modelling climate change (Intergovernmental Panel on Climate Chang [IPCC], 1995), but these models are large‐scale and cannot be used directly (IPCC, 2007). To solve this problem, stochastic weather generators, as a practical and popular method developed and successfully used for different regions of the world, are used (Bayatvarkeshi et al, 2020; Punyawansiri & Kwanyuen, 2020; Thao & Khoi, 2021). The Long Ashton Research Station Weather Generator (LARS‐WG) is one of the most widely applied weather generator models for climate change impact research, which is validated across the world and has been shown to perfectly simulate different climatological conditions (Semenov & Barrow, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…GCMs are the most reliable tools for modelling climate change (Intergovernmental Panel on Climate Chang [IPCC], 1995), but these models are large‐scale and cannot be used directly (IPCC, 2007). To solve this problem, stochastic weather generators, as a practical and popular method developed and successfully used for different regions of the world, are used (Bayatvarkeshi et al, 2020; Punyawansiri & Kwanyuen, 2020; Thao & Khoi, 2021). The Long Ashton Research Station Weather Generator (LARS‐WG) is one of the most widely applied weather generator models for climate change impact research, which is validated across the world and has been shown to perfectly simulate different climatological conditions (Semenov & Barrow, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The larger error for the precipitation compared to the other two parameters may be due to the large variation in precipitation (Hassan et al 2014). Given the results of the model, the maximum temperature was simulated better than the other two parameters and possessed higher accuracy (Bayatvarkeshi et al 2020). Although there is no complete correlation between the models and observations to date, the lack of quite correlation is not a barrier to the climate model's use.…”
Section: Cmip6 Models Validationmentioning
confidence: 96%
“…In order to test the performance of the LARS-WG model and ensure its ability to predict future precipitation in this study, the coefficient of determination (R 2 ) and the root-mean-square error (RMSE) were employed to compare observed and simulated rainfall data (Hassan et al 2014;Bayatvarkeshi et al 2020;Koshi et al 2021). R 2 is a dimensionless measure whose optimal value is one, as shown in Equation ( 2).…”
Section: Lars-wg Model Performance Evaluationmentioning
confidence: 99%